A versatile modular plant for converting biogas into advanced biofuels - Francesco Negri; Matteo Fedeli; Massimo Barbieri; Flavio Manenti (Invention Disclosure)
The patented technology is a novel, portable, non-invasive, and flexible technical solution for converting biogas into valuable chemical compounds, such as bio-methanol and bio-dimethyl ether (bio-DME). It consists of compact modules, connected to each other through a flange-valve-flange system, to be installed downstream an existing traditional biogas plant.The two main sections of the module are those of reforming and synthesis: in the first the biogas is converted into bio-syngas (H2/CO/CO2), while in the second the bio-syngas is transformed into advanced biofuels such as bio-methanol and bio-DME. Parts of the synthesis module can always be changed with small investments to switch the final products, according to local market needs and price volatilities. Downstream at the synthesis section, it is possible to add a module for the separation and the purification of the chemical products.The technology has been validated at the 0.15 MWe industrial scale.